Systematic Literature Review: Hubungan antara Self-Efficacy dengan Kemampuan Pemahaman Konsep Matematis Siswa - Sofyan Husein Nasution; Meiliasari Meiliasari; Wardani Rahayu (International Forum of Researchers and Lecturers, 2024)
This research aims to explain a review of the relationship between Self-efficacy and the ability to understand mathematical concepts, and how to develop and measure student Self-efficacy. In this research, the Systematic Literature research method was used which aims to obtain data from relevant research. With research sources coming from Google Scholar, Researchgate, Scopus, Syntax, and DOAJ. In this research, 17 reference sources were collected to obtain data and information. Information collected regarding differences in mathematical concept abilities in students' Self-Efficacy criteria, Development of Self-Efficacy in students in mathematics learning, Impact of students' Self-Efficacy on their ability to understand mathematical concepts, Measurement techniques (Indicators) of Self-Efficacy Efficacy of students' understanding of mathematical concepts. From the data collected, it was found that the technique that is often used is the Bandura technique. To develop self-efficacy in mathematics learning, you can focus on learning objectives, adding learning models, as well as 4 triggers, including: Mastery of experience, represented experience, social persuasion, and physical and affective conditions. In activating or applying these abilities, self-efficacy can have a positive impact on learning for students through external and internal learning activities of individual students. And self-efficacy is also useful in maintaining students' resilience in answering difficult questions, as well as understanding the concepts more deeply.